2020
DOI: 10.1038/s41598-020-61762-0
|View full text |Cite
|
Sign up to set email alerts
|

Glacier algae foster ice-albedo feedback in the European Alps

Abstract: the melting of glaciers and ice sheets is nowadays considered a symbol of climate change. Many complex mechanisms are involved in the melting of ice, and, among these processes, surface darkening due to organic material on bare ice has recently received attention from the scientific community. The presence of microbes on glaciers has been shown to decrease the albedo of ice and promote melting.Despite several studies from the Himalaya, Greenland, Andes, and Alaska, no quantitative studies have yet been conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 70 publications
2
45
1
Order By: Relevance
“…Albedo measurements from the upper ablation area of Haig Glacier over the period 2002-2017 indicate significant interannual variability in mean melt-season and glacier ice albedo, but there is no temporal trend in surface albedo over this period. This runs counter to documented albedo reductions elsewhere (Oerlemans et al, 2009;Mernild et al, 2015;Williamson et al, 2019;di Mauro et al, 2020), and to anecdotal evidence of darkening glaciers in the Canadian Rockies. The result may just be specific to the Haig Glacier AWS site; we do not have data to constrain albedo trends on the lower glacier, where changes and melt 550 feedbacks have been strongest over the observation period.…”
Section: Conclusion 545contrasting
confidence: 79%
“…Albedo measurements from the upper ablation area of Haig Glacier over the period 2002-2017 indicate significant interannual variability in mean melt-season and glacier ice albedo, but there is no temporal trend in surface albedo over this period. This runs counter to documented albedo reductions elsewhere (Oerlemans et al, 2009;Mernild et al, 2015;Williamson et al, 2019;di Mauro et al, 2020), and to anecdotal evidence of darkening glaciers in the Canadian Rockies. The result may just be specific to the Haig Glacier AWS site; we do not have data to constrain albedo trends on the lower glacier, where changes and melt 550 feedbacks have been strongest over the observation period.…”
Section: Conclusion 545contrasting
confidence: 79%
“…Alternatively, some contribution of albedo reduction in this region may be attributable to the presence of algae and microbial communities in snow and cryoconite (e.g. Di Mauro and others, 2020) thereby enhancing the positive feedback of glacier melting. Again, to date, no known studies have demonstrated this within the central Andes and it is unclear to what extent such glacier-algae communities affect small mountain glaciers of the semi-arid region.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the relative complexity of the model, it is best-suited to catchment-scale applications where high-quality in situ data are already available to better understand the volume and spatial and temporal distribution of meltwater production throughout the melt season. Since we derive distributed surface albedo from Landsat 8 data, the model also has wide applicability to further investigate the impacts of the darkening of mountain glaciers (Naegeli and Huss, 2017; Di Mauro and others, 2020) and ice sheets (Box and others, 2012; Bond and others, 2013; Dumont and others, 2014; Williamson and others, 2019; Tedstone and others, 2020).…”
Section: Discussionmentioning
confidence: 99%